Wavefront shaping through emulated curved space in waveguide settings - Chong Sheng (Nature Portfolio, 2016)
Wavefront shaping is typically carried out outside the medium within which the beam is propagating. Sheng et al.exploit concepts inspired by General Relativity for wavefront shaping within optical waveguide settings, constructing narrow collimated beams and shape-preserving beams accelerating on arbitrary trajectories